(3GdeHShWs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3Ydj CcHQ Hf ejQRG HGHG GdNhfSGQjs)
(3ChdgG (B:s
.. (3aCeG GdEHd ajLhR GdeSGHbI dbhdg JYGdi (B{ (3aeG ChLaJe Ydjg ef Njd hdG QcGH (B} (3hGdNHQ CjVG hGdQcGH GdEHd hdCf GdfHj Udi Gddg Ydjg hSde SGHb HfGbJg GdYVHGA hCeG GdNjQ abGd bhe dG jLhR dCfg djS eeG jcfR (B...s
(3BNQgG (B:s
... (3bhdg GdMb YjfG ddeHjY aEf HGY adG cdGe hEf gdd GdYjf bHd GdHjY bGd bhe jchf ef VeGf ef Ydjg GdOjf dCf gPg GdYjf bHVJ dGSJjaGA GdOjf ef KefgG hcGfJ CeGfI cGdQgf hbGd BNQhf Ydjg VeGfg (B.. (3bO Je cJGH GdOYGhi hGdHjfGJ (B.s
(3JHUQI GdYfhGf (B:s
(3aj GdaQhYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\84s
(3cTa GdXfhf (B2\1581s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis